Light-induced translation of motorized molecules on a surface - Saywell, Alexander; Bakker, Anne; Mielke, Johannes; Kumagai, Takashi; Wolf, Martin; García-López, Víctor; Chiang, Pinn-Tsong; Tour, James M.; Grill, Leonhard (American Chemical Society, 2016)
Molecular machines are a key component in the vision of molecular nanotechnology and have the potential to transport molecular species and cargo on surfaces. The motion of such machines should be triggered remotely, ultimately allowing a large number of molecules to be propelled by a single source, with light being an attractive stimulus. Here, we report upon the photoinduced translation of molecular machines across a surface by characterizing single molecules before and after illumination. Illumination of molecules containing a motor unit results in an enhancement in the diffusion of the molecules. The effect vanishes if an incompatible photon energy is used or if the motor unit is removed from the molecule, revealing that the enhanced motion is due to the presence of the wavelength-sensitive motor in each molecule.